The Unleashing Your Writing Potential: Enhancing Skill With Mind Mapping Technique - Ni Made Sri Rahayu; Ni Luh Supartini; Putu Sri Darmayanti (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
Abstract This research aimed to find a way to improve writing skills through mind mapping. This study was conducted in three cycles following the procedures for action research, namely planning, implementing, observing, and reflecting. This research used pre experimental research consisting of two cycles, and each cycle consisted of two sessions. Besides, the research was preceded by an initial reflection to know the subjects' pre-existing ability in the pre-cycle. The whole process of the present study consisted of three main phases: pre-cycle, cycle I, and cycle II, in which each cycle consisted of four interconnected activities: planning, action, observation, and reflection. The researcher used a pre-test, post-test, and questionnaire to analyse the significant improvement. The researcher used statistics using the main score formula to analyse the data. The finding shows that the mean post-test score is higher (87) than the pre-test score (70). Based on these results of the post-test, the questionnaire result showed positive responses from the subjects toward implementing the mind mapping technique. In other words, this study establishes that 8th-grade students' writing ability in SMPN 3 Abiansemal, Badung, Bali could be enhanced by her mind mapping technique. Keywords: Improving , Mind Mapping Technique , Writing Skill , English language